2023
DOI: 10.3390/toxics11070624
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Polydispersity of Volcanic Ash Nanoparticles in Synthetic Lung Fluid

Abstract: The inhalation of natural nanoparticles (NPs) emitted from volcanic activity may be a risk to human health. However, the literature rarely reports the fate and response of NPs once in contact with lung fluids. In this work, we studied the particle size distribution of ashfall from Popocatépetl volcano, Mexico. The collected ashes (n = 5) were analyzed with scanning electron microscopy (SEM) to obtain the elemental composition and morphology, and to determine the size of the ash particles using ParticleMetric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Anthropogenic particles are characterized by more spherical shapes due to combustion processes [13,[58][59][60][61]. Particle size and shape of samples could result from the presence of different mineralogical phases [25]. Many researchers have stated that particle shape may have great impact on its toxicity [13,[58][59][60][61].…”
Section: Limitations Of This Study and Generalization Of Its Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropogenic particles are characterized by more spherical shapes due to combustion processes [13,[58][59][60][61]. Particle size and shape of samples could result from the presence of different mineralogical phases [25]. Many researchers have stated that particle shape may have great impact on its toxicity [13,[58][59][60][61].…”
Section: Limitations Of This Study and Generalization Of Its Resultsmentioning
confidence: 99%
“…The results of their study proposed an interaction between nanoparticles and lung fluids, particularly within the alveolar macrophage region. [25]. Kalaiarasan at al.…”
Section: Lung Deposited Surface Areamentioning
confidence: 99%
“…Despite their negligible contribution to the particle mass, the toxicity of UFPs and their complex chemical composition may be greater than particles such as PM 10 or PM 2.5 [10,11]. The smaller size of UFPs enables them to acquire a higher rate of deposition into the deeper region of the lungs [12,13] and to possess the ability to cross the air-liquid interface into the systemic circulation by which they can reach distal organs [14,15]. Epidemiological studies have reported associations between respiratory mortality and other health effects with exposure to UFPs [16].…”
Section: Introductionmentioning
confidence: 99%